Community-Based Public Relations and Destination Branding: Evidence from Bobung Tourism Awareness Group - Azalia Wasithotul ‘Ulaa; Imam Sumarlan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
In the increasingly competitive tourism industry, destination branding requires not only promotional activities but also meaningful engagement with local communities. This study examines how community-based public relations practices contribute to destination branding through stakeholder relationship management and community empowerment within the Bobung Working Group (Pokja). Drawing upon Relationship Management Theory, particularly the dimensions of trust, commitment, satisfaction, and mutual control, as well as Scheyvens’ Community-Based Tourism Empowerment Framework, this research employs a descriptive qualitative approach. Data were collected through in-depth interviews with Pokja members, local residents, tourists, and tourism office representatives, and were analyzed using thematic analysis. The findings reveal that community-based public relations foster trust-based relationships, strengthen stakeholder commitment, enhance community and tourist satisfaction, and facilitate participatory decision-making processes. Simultaneously, tourism development generates economic opportunities, strengthens community identity and confidence, promotes social cohesion, and increases local participation in tourism governance. These relational and empowerment processes collectively contribute to the formation of a distinctive destination brand characterized by cultural authenticity, community participation, and local craftsmanship. The study concludes that destination branding in community-based tourism settings is not merely a communication outcome but a reflection of sustainable relationships and empowered local communities.